Occurrence of Protozoan Parasites From Climbing Perch, Anabas Testudineus From Open Waters of Bangladesh (Bangladesh Journal of Zoology, 2020)
The study was conducted to identify the protozoan parasites and to determine their occurrence and diversity in climbing perch, Anabas testudineus (Bloch, 1972). The sample fish species were collected from mid-October, 2018 to end of the December 2018 from freshwater bodies of Mymensingh, Kishoregonj, Faridpur and Jashore districts. Three species of myxozoa (Henneguya mystusia, Henneguya qadrii and Henneguya acerinae) and 4species of ciliophora (Trichodina acuta, Trichodina spp., Epistylis lwoffi and Amphileptus disciformis) were identified in A. testudineus. Approximately 76.19% of total fish species were infected by at least one of the parasites with average load of 71.38±32.26 per infected host. Myxozoans (97.55%) were clearly dominant group than chiliophorans (2.45%). The highest prevalence of parasitic infection was observed in the fishes of Mymensingh (100%) and lowest in Jashore (40%).The association of parasitic infection of H. mystusia (p=0.018), H. qadrii (p= 0.00044), H. acerinae (p=0.003), Trichodina acuta (p= 0.052)and A. disciformis (p= 0.023) with study area was statistically significant. Protozoan parasites were most abundant in gills of the hosts. Shannon Diversity Index indicated that hosts were not infested by more parasites and the parasite community was poorly diverged in all study sites but Simpson’s Diversity Index showed that, parasites community was moderately diverged in host fish of Mymensingh area and in rest of areas they were poorly diverged.Bangladesh J. Zool. 48(1): 127-140, 2020